New species of Terebellides (Polychaeta: Trichobranchidae) indicate long-distance dispersal between western South Atlantic deep-sea basins - Schüller, M.; Hutchings, P. A. (Zootaxa, 2012)
During the expedition DIVA 3 in summer 2009, six new species of the genus Terebellides (Trichobranchidae) were discoveredfrom the deep Argentine and Brazil basins. Five of these (Terebellides gingko sp. n., Terebellides banalis sp. n., Terebellidesbulbosa sp. n., Terebellides concertina sp. n., Terebellides diva sp. n.) are formally described herein; the sixth species is onlybriefly described as it was represented by only a single specimen. While most species were represented by a few specimensfrom a single basin, T. gingko sp. n., was found in relative high abundances in both basins. Molecular analyses of 16S rDNAsequences confirmed the long-distance distribution of this species. Although branchiae are lost in the majority of specimensfound, all new species can clearly be separated from each other and Terebellides species formerly reported for shallow westernSouth Atlantic waters by the relationships between head structures and anterior segments, and the shape of thoracic and anterior uncini, presenting evidence for a diverse and previously undescribed diversity of Trichobranchidae in the world’s deep seas.